2017
DOI: 10.1002/nbm.3728
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of pancreatic diffusion MRI by tissue characteristics: what are we weighting for?

Abstract: Diffusion-weighted imaging holds the potential to improve the diagnosis and biological characterization of pancreatic disease, and in particular pancreatic cancer, which exhibits decreased values of the apparent diffusion coefficient (ADC). Yet, variable and overlapping ADC values have been reported for the healthy and the pathological pancreas, including for cancer and other benign conditions. This controversy reflects the complexity of probing the water-diffusion process in the pancreas, which is dependent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…A 3D T 1 -weighted MPRAGE (magnetization prepared rapid acquisition gradient echo) sequence (T R /T E = 2300 ms/2.32 ms; echo spacing time = 7 ms; flip angle = 8°; T I = 900 ms; parallel imaging using generalized autocalibrating partial parallel acquisition (GRAPPA) acceleration factor 2; voxel size = 1 × 1 × 1 mm 3 ; FOV = 300 × 240 mm 2 ) was acquired for anatomical orientation. DW images were acquired using a fat-saturated EPI (echo-planar imaging) sequence with twice refocused diffusion preparation, as reported in Reference 24 (T R = 4100 ms; T E = 90 ms; echo spacing = 0.68 ms; bandwidth in EPI readout direction = 1685 Hz/px; GRAPPA acceleration factor = 2; partial Fourier = 7/8; FOV = 228 × 228 mm 2 ; voxel size = 2 × 2 × 2 mm 3 ; number of slices = 24; b-values 0, 5,10,20,35,55,80,110,150,200, 300, 500, 750, 1000, 1200 s/mm 2 ; 20 diffusion-encoding directions). The use of a bipolar diffusion preparation mitigated or prevented image distortions due to eddy current effects.…”
Section: Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D T 1 -weighted MPRAGE (magnetization prepared rapid acquisition gradient echo) sequence (T R /T E = 2300 ms/2.32 ms; echo spacing time = 7 ms; flip angle = 8°; T I = 900 ms; parallel imaging using generalized autocalibrating partial parallel acquisition (GRAPPA) acceleration factor 2; voxel size = 1 × 1 × 1 mm 3 ; FOV = 300 × 240 mm 2 ) was acquired for anatomical orientation. DW images were acquired using a fat-saturated EPI (echo-planar imaging) sequence with twice refocused diffusion preparation, as reported in Reference 24 (T R = 4100 ms; T E = 90 ms; echo spacing = 0.68 ms; bandwidth in EPI readout direction = 1685 Hz/px; GRAPPA acceleration factor = 2; partial Fourier = 7/8; FOV = 228 × 228 mm 2 ; voxel size = 2 × 2 × 2 mm 3 ; number of slices = 24; b-values 0, 5,10,20,35,55,80,110,150,200, 300, 500, 750, 1000, 1200 s/mm 2 ; 20 diffusion-encoding directions). The use of a bipolar diffusion preparation mitigated or prevented image distortions due to eddy current effects.…”
Section: Mrimentioning
confidence: 99%
“…15,16 The thermally driven mobility of water molecules as well as the flow of water molecules into randomly distributed capillaries and tubular structures result in an intra-voxel dephasing of the transverse magnetization, which contributes to the signal loss. [17][18][19] Besides providing measures of diffusion anisotropy and of the total degree of diffusion in the voxel, the sampling of the DWI signal within an optimal range of b-values and along at least six non-collinear diffusion-encoding directions within one single scan potentially allows tissue differentiation in terms of cellularity, [20][21][22] microstructure, 23,24 and perfusion. 25 The intrinsic T 2 weight of the low b-value volumes offers an additional tissue-specific element for classification.…”
mentioning
confidence: 99%
“…5,14 The main MR-based procedure clinically recommended for the (relatively late-stage) diagnosis of PDAC remains magnetic resonance cholangio pancreatography (MRCP), a long-echo-time sequence that leaves solely the biliary ducts in the image, and can therefore point towards the presence of tumors if they distort the ducts' normal shapes. 15 A case has also been made for the inclusion of diffusion-weighted imaging (DWI) in these diagnoses 10,16 ; apparently, due to the fibrotic nature of the stroma and the tumor's high cellularity, 17 these will have lower diffusivity and appear bright in DWI data. 16,18,19 This, however, has also been described as not always being the case for a large study of human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…15 A case has also been made for the inclusion of diffusion-weighted imaging (DWI) in these diagnoses 10,16 ; apparently, due to the fibrotic nature of the stroma and the tumor's high cellularity, 17 these will have lower diffusivity and appear bright in DWI data. 16,18,19 This, however, has also been described as not always being the case for a large study of human subjects. 20 Some diffusion tensor imaging (DTI) studies have demonstrated that the tumor's stroma has some preferential orientation.…”
Section: Introductionmentioning
confidence: 99%
“…number of b-values and modelling methods for ADC/IVIM) 105 remain a major barrier to deriving diagnostic quantitative cut-off values that can be applied across different sites and scanners. 106 The lack of standardized protocols is a common barrier for methods such as T 1 mapping (where different methods can yield small but significant differences in quantification) and DCE MRI. Finally, quantitative MR sequences must be time-efficient to enable them to be included within normal anatomical imaging protocols.…”
Section: Chouhan Et Almentioning
confidence: 99%